Islamic Civil Society and Conflict Resolution Muhammadiyah’s Challenges Towards The Dynamics of Malaysia-Indonesia Relationship - Muhammad Zahrul Anam (Universitas Muhammadiyah Yogyakarta, 2013)
This paper explains why Muhammadiyah, as the biggest Islamic movement in Indonesia, seems to be “silent” in dealing with tension between Indonesia and Malaysia. There are several potential factors of conflict: boundary, culture and migrant workers. Furthermore, migrant worker and boundary may cause casualties. In this regard, Muhammadiyah with its developed and extended membership, organizational structure and international network should take major part in the conflict resolution. However, conflict resolution capacity to respond the tension is becoming problem for Muhammadiyah itself. This paper uses a theory put forward by Becky Nesbitt on the role of INGOs and NGOs in three levels of conflict, namely,latent conflict, escalating hostilities conflict and peace building. The first and second level of conflict require advocacy and the third level employs people empowerment in reducing further conflict. To enhance the capacity, Muhammadiyah needs to transform and formulate a strategic action. In addition, it also needs to improve cooperation, research and network with the international leader and community.